Cutie and the boxer [videorecording (DVD)] - Heinzerling, Zachary; Shimizu, Yasuaki; Shinohara, Ushio, 1932-; Shinohara, Noriko, 1953- (Anchor Bay Entertainment, 2014)
In New York City in 1969, nineteen-year-old art student Noriko fell in love with 41-year-old avant-garde artist Ushio Shinohara and put her career on hold to marry and support this rising star of the Manhattan art world. But 40 years later and still struggling, Ushio remains consumed with reinforcing his legacy via his 'boxing' paintings, while Noriko is now finding her own creative voice through a series of drawings.